Early intervention with eye movement desensitisation and reprocessing (EMDR) therapy to reduce the severity of posttraumatic stress symptoms in recent rape victims: study protocol for a randomised controlled trial. Issue 1 (31st December 2019) - Covers, Milou L. V.; De Jongh, Ad; Huntjens, Rafaële J. C.; De Roos, Carlijn; Van Den Hout, Marcel; Bicanic, Iva A. E.
ABSTRACT: Background: It is estimated that more than 40% of rape victims develops a posttraumatic stress disorder (PTSD), a statistic that is relatively high compared to other types of trauma. PTSD can affect the victims' psychological, sexual, and physical health. Therefore, there is an urgent need for early interventions to prevent the onset of PTSD in this target group. Objective: This randomised controlled trial (RCT) examines the efficacy of early Eye Movement Desensitisation and Reprocessing (EMDR) therapy aimed to reduce the severity of posttraumatic stress symptoms in victims of recent rape. Methods: Subjects (N = 34) are individuals of 16 years and older who present themselves within 7 days post-rape at one of the four participating Sexual Assault Centres in the Netherlands. The intervention consists of two sessions of EMDR therapy between day 14 and 28 post-rape, while the control group receives treatment as usual, consisting of careful monitoring of stress reactions by a case-manager across two contacts during 1-month post-rape. Baseline assessment, posttreatment assessment and follow-up assessments at 8 and 12-weeks post-rape will be used to assess the development of posttraumatic stress symptoms. In addition, the efficacy of the intervention on psychological and sexual functioning will be determined. Linear mixed model analysis will be used to explore the differences within and between the EMDR group and control group at the various time points. Conclusions: The results of this RCT may help the dissemination and application of evidence-based preventative treatments for PTSD after rape. HIGHLIGHTS: Rape victims are at high risk for developing PTSD. Research has not yet found effective, evidence-based early post-rape interventions. This study examines the effectiveness of EMDR in reducing posttraumatic stress symptoms after rape. The RCT examines a variety of psychological problems during three months after rape.